Negotiation of Indonesian Orthodox Christian Identity in the Context of Interfaith Communication in Depok - Cassandra Fitriani Madjegu; Frengki Napitupulu (Journal of Social Research, 2023)
This paper describes the experience of negotiating the identity of Indonesian Orthodox Christians in the context of inter-religious communication in Depok. The discussion is intended to find out the identity negotiations carried out by the Orthodox Christian Community during the presence of religious people in Depok so that differences of opinion and understanding between religious communities can be mediated and to find out the obstacles in maintaining communication between Indonesian Orthodox Christians and Protestant, Catholic and Muslim Christians. This research uses qualitative methods which are carried out using a phenomenological approach, while phenomenological research is a type of qualitative research that sees and hears closely and in detail regarding individual understanding of the experiences needed. So, this study aims to find out and confirm the 10 main assumptions in negotiating identity in the context of inter-religious communication in Depok and knowing the obstacles to maintaining inter-religious communication in Depok. Data were collected by interview, observation, and document methods. The validity of the data was obtained by means of triangulation, examination of respondents, and assessments from supervisors. Data were analyzed by (1) data reduction, (2) data presentation, and (3) drawing conclusions.